Intelligent home appliances control system (IHAC) / Wan Azlan Wan Yunus - Wan Yunus, Wan Azlan (1999)
The arrival of the next millennium requires the home appliances to become more intelligent and sophisticated. This paper describes an Intelligent Home Appliances Control System (IHAC) which uses microcontroller to perform the controlling process and decode the signal transmitted from the Infrared (IR) remote control (RP420) via parallel port. A simple microcontroller i.e. PIC16F84 from Microchip Corporation has been chosen to implement the decoding process, as it is suitable for the project and easy to use. A simple appliance i.e. light dimmer has been chosen to illustrate the application of the system. Each modules of the system had been tested successfully.